Intra-good trade in Germany: a first look at the evidence. Issue 57 (8th December 2017) - Wagner, Joachim
ABSTRACT: This article contributes to the literature by using newly released comprehensive transaction-level data on all exports and imports to document facts about the amount of intra-good trade – the simultaneous export and import of identical goods by one firm – in Germany. Combined data for trade transactions and for characteristics of a representative large sample of trading firms are then used to report differences between firms that export and import different goods only ( inter-good traders ) and firms that engage in the simultaneous export and import of identical goods ( intra-good traders ). We find that the share of intra-good trade in total trade was some 17% in Germany in 2012. Intra-good trade matters. This share differs widely between broadly defined groups of goods and between industries. Controlling for detailed industry affiliation, intra-good traders differ significantly from inter-good traders – they are larger, more human capital intensive, more productive, have a higher R&D intensity and are more profitable. The data, however, are not rich enough to reveal the direction of causality between intra-good trade and firm performance and to investigate empirically the reasons why some firms engage in intra-good trade.